2001
DOI: 10.1002/1438-9312(200102)103:2<102::aid-ejlt102>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterol-ester-enriched spreads as an example of a new functional food

Abstract: A series of new human clinical trials have been conducted on the efficacy of plant sterols given as plant sterol-es-Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 23 publications
0
21
0
5
Order By: Relevance
“…Plant-derived sterols have been reported to decrease LDL cholesterol level in blood [58]. The quality of vegetable oil is correlated with its sterol contents.…”
Section: Classification Of Natural Biomolecules Of Z Lotusmentioning
confidence: 99%
“…Plant-derived sterols have been reported to decrease LDL cholesterol level in blood [58]. The quality of vegetable oil is correlated with its sterol contents.…”
Section: Classification Of Natural Biomolecules Of Z Lotusmentioning
confidence: 99%
“…A notable functional food and nutraceutical innovation associated with reductions in blood cholesterol is the incorporation of plant sterols and stanols (phytosterols) into foods, such as vegetable oil spreads and dairy drinks, and non‐prescription pills (Law, 2000; Ntanios, 2001; Rudkowska and Jones, 2007). Phytosterols are chemically similar to cholesterol and, when consumed at adequate levels, can inhibit exogenous and endogenous cholesterol in the gastrointestinal tract (Maki et al.…”
Section: Introductionmentioning
confidence: 99%
“…A notable functional food and nutraceutical innovation associated with reductions in blood cholesterol is the incorporation of plant sterols and stanols (phytosterols) into foods, such as vegetable oil spreads and dairy drinks, and non-prescription pills (Law, 2000;Ntanios, 2001;Rudkowska andJones, 2007). et al, 2003) have demonstrated that regular consumption of phytosterols can lower total and LDL cholesterol (see reviews by Ling and Jones, 1995;Law, 2000;Rudkowska and Jones, 2007), and thereby decrease the risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the carotenoid-lowering effect, no other nutritionally-relevant changes or other abnormalities were evident in several randomised trials of plant sterol or stano I margarines in humans (see Ntanios 2001), some of which lasted for one year .…”
Section: Effect Of Phytosterols In Lowering Blood Levels Of Carotenoimentioning
confidence: 99%